Modification of Al2O3-Based Membranes with Carbon Black for Enhanced Hydrogen Permeation - Montree Hankoy; Mana Rodchom; Supawan Vichaphund; Duangduen Atong; Jianfeng Zhang; Mettaya Kitiwan; Phacharaphon Tunthawiroon (Technologies, 2025)
This work presents the development and characterization of alumina–carbon black (ACB) composite membranes for enhanced hydrogen separation performance. A series of membranes containing 0–3.0 wt.% carbon black was fabricated via high-temperature sintering and systematically investigated with respect to their structural, morphological, mechanical, and gas separation properties. The addition of carbon black significantly influenced membrane microstructure, promoting pore network formation, increasing specific surface area, and enhancing gas transport. Gas permeation tests using H2 and N2 revealed that all ACB membranes exhibited higher hydrogen permeance than the pure Al2O3 membrane. Notably, the ACB3.0 specimen demonstrated the highest H2 permeance of 508 × 10−6 mol m−2 s−1 Pa−1 at 303 K, which is nearly four times greater than the unmodified membrane. At an elevated temperature (773 K), H2/N2 selectivity improved with increasing carbon black content, with ACB3.0 achieving a maximum selectivity of 3.82, exceeding the theoretical Knudsen value, suggesting a synergistic contribution of Knudsen diffusion and surface diffusion. These results demonstrate that carbon black is a cost-effective and versatile additive for modifying ceramic membranes, offering a promising route for advancing hydrogen purification technologies in industrial applications.
Keywords: Catalysts for Methane Reforming; Membrane Separation and Gas Transport; Advancements in Solid Oxide Fuel Cells